A Smaller Circle - Bhikha, Nasira (Rhodes University, Faculty of Humanities, School of Languages)
My thesis is a collection of prose forms weaving my identity as a South African woman of colour, my observations of life through personal, cultural and sociological lenses, where traditions are constantly challenged and evolving. The collection focuses on the untold and unresolved, using fiction as a tool of pushback and psychological reflection. I am motivated by writers who use what I would term reflective expressionism to evoke empathy by tapping into innate, universal emotions. In particular Tiff Holland's vivid telling of family in the novella Betty Superman where she navigates complex relationships, and bell hooks' memoirs Bone Black: Memories of Girlhood written as poetic vignettes in fluctuating points of view to draw attention to the intricacies of social structures. Joanna Walsh's Vertigo has strongly influenced my approach to writing through her compelling imagery and use of motif in fragmented prose that delves into the psyche of her characters. I am also inspired by Lidia Yuknavitch's visceral use of language, identifying with her invitation: "You deserve to sit at the table. The radiance falls on all of us."
Keywords: Creative writing (Higher education) -- South Africa; South African fiction (English) 21st century; Short stories, South African (English) 21st century; Diaries -- Authorship; Autobiography; Short stories, English History and criticism; American fiction History and criticism; Mexican fiction History and criticism